2020
DOI: 10.1177/0363546520969985
|View full text |Cite
|
Sign up to set email alerts
|

Hip Arthroscopic Surgery in the Context of Femoroacetabular Impingement Syndrome, Labral Tear, and Acetabular Overcoverage: Minimum 5-Year Outcomes With a Subanalysis Against Patients Without Overcoverage

Abstract: Background: Improvement in patient-reported outcomes (PROs) has been reported in the short term after hip arthroscopy for femoroacetabular impingement syndrome (FAIS) and labral tear in the setting of acetabular overcoverage. Yet, there is a paucity of information in the literature on midterm PROs. Purpose: To (1) report minimum 5-year PROs in patients who underwent primary hip arthroscopy for FAIS and acetabular labral tears in the context of acetabular overcoverage and (2) compare outcomes with those of a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…Labral tears were repaired, selectively debrided, or reconstructed according to the extent of tearing and labral characteristics. 18 An acetabuloplasty >2 mm was used to address pincer-type morphology (LCEA >40°) 32 ; otherwise, a minor acetabular rim trimming was performed to provide an adequate bleeding bony bed for labral repair/reconstruction healing. Femoroplasty was used to address cam-type morphology (alpha angle >55°).…”
Section: Methodsmentioning
confidence: 99%
“…Labral tears were repaired, selectively debrided, or reconstructed according to the extent of tearing and labral characteristics. 18 An acetabuloplasty >2 mm was used to address pincer-type morphology (LCEA >40°) 32 ; otherwise, a minor acetabular rim trimming was performed to provide an adequate bleeding bony bed for labral repair/reconstruction healing. Femoroplasty was used to address cam-type morphology (alpha angle >55°).…”
Section: Methodsmentioning
confidence: 99%
“…8,9 While focal pincer FAI can be treated with arthroscopic techniques effectively, global pincer FAI once required open surgery due to the technical difficulties of joint distraction, decreased access to the central compartment, and insufficient access to the posterior acetabulum. 10 Nevertheless, with the development of arthroscopic instrumentation and techniques, studies in recent years have shown that patients with global pincer FAI can be treated arthroscopically with satisfactory outcomes. 11 However, controversy remains whether the patients with global pincer have equivalent outcomes compared with patients with focal pincer.…”
Section: Introductionmentioning
confidence: 99%
“…10,26,28,81 Arthroscopic surgery of the hip has become an effective tool to address hip pathology, 32,47 proving satisfactory results in patient-reported outcomes (PROs) in mid-and long-term studies. 25,37,52,63,72 This has been achieved thanks to the development of novel techniques that offer safe and reproducible procedures with consistent results. 49,51,55 However, patients with workers' compensation (WC) claims undergoing surgery have been associated with inferior outcomes when compared with other patients without such claims.…”
mentioning
confidence: 99%
“…10,26,28,81 Arthroscopic surgery of the hip has become an effective tool to address hip pathology, 32,47 proving satisfactory results in patient-reported outcomes (PROs) in mid- and long-term studies. 25,37,52,63,72 This has been achieved thanks to the development of novel techniques that offer safe and reproducible procedures with consistent results. 49,51,55…”
mentioning
confidence: 99%